Innovative dairy cow management to improve resistance to metabolic and infectious diseases during the transition period - Lacasse, P.; Vanacker, N.; Ollier, S.; Ster, C. (Research in veterinary science, 2018)
The incidence of metabolic and infectious diseases varies greatly during the lactation cycle. Most new cases of clinical mastitis appear at the beginning of lactation, and the incidence increases with the level of milk production. In addition to mastitis, many other infectious diseases become clinically apparent during the first 2weeks of lactation. During this time, cows are in a negative energy balance and must mobilize body reserves to balance the deficit between food energy intake and energy required for milk production. The relationships between energy deficit and metabolic diseases, such as ketosis and hepatic lipidosis, are well known. Furthermore, cows in energy deficit have a weakened immune system and are therefore more susceptible to infections. There is now good evidence that the increase in circulating non-esterified fatty acids impairs immune cell functions. Therefore, management approaches that reduce the negative energy balance and the increase in non-esterified fatty acids at the beginning of lactation are likely to improve resistance to infection. Improving the nutrient supply through periparturient nutritional management has been the subject of considerable research. However, another way to reduce the imbalance between nutrient supply and demand is to temporarily decrease the latter. In this review, we examine how management strategies such as conjugated linoleic acid feeding, prepartum milking, or limiting postpartum milk production could be used to reduce metabolic perturbations and immunosuppression during the transition period. At this stage, it appears that reducing the amount of milk harvested postpartum by means of partial milking in the first days after calving is the most promising approach to reduce metabolic stress and immunosuppression without compromising the productivity of high-yielding dairy cows. •High concentration of non-esterified fatty acids (NEFA) impairs immune cell functions.•Approaches that improve energy balance and the increase in NEFA during transition period are likely to improve resistance to infection.•It is possible to reduce the imbalance between nutrient supply and demand by temporarily decrease the latter.•Milking cow partially in the first days after calving is a promising approach to reduce metabolic stress and immunosuppression.